Comprehensive Evaluation of the Lower Eyelid Aging Process Among Asian Women. Issue 6 (22nd June 2022) - Cheng, Chun-Yu; Hu, Sindy; Chang, Shyue-Luen; Lee, Mei-Ching; Huang, Yau-Li
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Lower eyelid aging is a complicated process, and for that reason, a comprehensive assessment of the lower eyelid is important before treatment. OBJECTIVE: This study was conducted to analyze and assess the lower eyelid aging process between different age groups of Asian women. METHODS AND MATERIALS: The authors developed the comprehensive lower eyelid age rating scale (CLEARS). The rating scale contains 3 domains and each composed of 3 items. Individuals were evaluated by the age group starting with the third decade (20–29 years) through the seventh decade (60–69 years) by 2 dermatologists working independently. RESULTS: A total of 114 cases were evaluated. The total scores of CLEARS increased significantly between each adjacent age group. The scores of the snap test and the severity of fine lines, nasojugal groove, midcheek furrow, and eye bags increased significantly from the 3rd decade. The scores of the distraction test and the severity of palpebromalar groove and malar mound begin to increase with the 4th decade. Kappa coefficients of all items achieved moderate to substantial agreement. CONCLUSION: This study describes the lower eyelid aging process among Asian women by CLEARS assessment. Lower eyelid aging becomes progressively more notable beginning with the third decade.